Sistem Pendukung Keputusan Kontribusi Optimal pada Produk Pompa Air dan Mesin Mollen dengan Pendekatan Program Linier Metode Simplex - Dewi Handayani Untari Ningsih; Sunardi .; Arief Jananto (Dinamik, 2003)
Decision Support System couple the intellectual resource of individuals with the capabilities of the computer to improve the quality of decision. It's a computer based support system for management decision makers who deal with semi-structured problem. An integrated decision support system for use in an machine mollen product has been developed. It incorporates a linear Programming model that represents the contribution optimal and optimizes the production water pump and mollen machine. An optimization model is performed using a management scient model called linear programming approach in older to determine media selection. To use this model, the DSS needs ti interface with another software. Mathematical Programming is a technique used in mathematical models, particularly optimization models, to assist in decision making. The Simplex Method is "a systematic procedure for generating and testing candidate vertex solutions to a linear program." (Gill, Murray, and Wright, p. -137) It begins at an arbitrary corner of the solution set. At each iteration, the Simplex Method selects the variable that will produce the largest change towards the minimum (or maximum) solution. The  development of computer programs to be used as Decision Support Systems involves several tasks such as mathematical modeling, technical and data collection and development of a user friendly interface.